Safety and Complications of Interventional Endoscopic Ultrasound - Monica Saumoy; Michel Kahaleh (Korean Society of Gastrointestinal Endoscopy, 2018)
Endoscopic ultrasound (EUS) has become an essential tool for the diagnostic and therapeutic intervention of gastrointestinal diseases. Beyond the drainage of fluid collections, it enables decompression of inaccessible bile and pancreatic ducts, the gallbladder, and the creation of anastomosis within the gastrointestinal tract using fully lumen-apposing stents. This review explored the safety and efficacy of these novel procedures and discussed the training pathway that is necessary to perform them efficiently and safely.